Bułgarska misja Tadeusza S. Grabowskiego, wysłannika odradzającej się Polski i dwujęzyczne wydanie Ankiety bułgarskiej w sprawie polskiej (1915–1916) - Albena Popowa (Postscriptum Polonistyczne)
Years 2011 and 2015 are two anniversaries both linked with the name of Tadeusz Grabowski – 130th anniversary of the Polish professor and diplomat and 100th anniversary of the Bulgarian questionnaire on the Polish issue (1915–1916) – an important document about PolishBulgarian relations. Prof. Magda Karabelova initiated the two publications about Prof. Grabowski and his work in Bulgaria – biography of Tadeusz Grabowski and the first Bulgarian translation of the Bulgarian questionnaire on the Polish issue (1915–1916). These two publications are presented in the article. Prof. Tadeusz Grabowski has played a very important role in PolishBulgarian relations, both as a scientist and as a polish ambassador in Bulgaria. Probably the Questionnaire is one of his most important publications – a document not only about the diplomatic mission of Poland at that time but also a record of the vision of the highest Bulgarian public figures about the political situation and relations with Poland. A careful reading of both surveys leaves no doubt that it is worth the efforts of Prof. Karabelova to present them to the Bulgarian audience. The mission of Prof. Tadeusz Grabowski has influenced not only PolishBulgarian relations, but also our understanding of the political and social situation in the country.